Effectiveness of acupuncture as an adjunct treatment for women with postnatal depression: a systematic review protocol. (November 2018) - Wang, Carol Chunfeng; Zhu, Ruifang; Ge, Li; Tufanaru, Catalin; Bayes, Sara; De Jong, Gideon
Abstract : Review question: The review question is: what is the best available evidence on the effectiveness of acupuncture as an adjunct treatment for women with postnatal depression?